دور الولايات المتحدة الأمريكية في الحرب على سورية - الشاهر, شاهر (Latakia University Journal - Economic and Legal Sciences Series, 2018)
لم تحدث عملية ضرب أمن واستقرار سورية بشكل مباشر، بل خضعت لعدّة مراحل تمهيدية عكست بشكل أو بأخر مدى أهمية وصعوبة استهداف سورية، نظراً لتداخل بعض الملفات الإقليمية والدولية في سورية، فكان لا بد أنّ يتم ذلك عبر العديد من الخطوات، فقد سعت السياسة الأميركية إلى تحويل اتجاه الصراع في المنطقة من صراع عربي- إسرائيلي إلى صراع طائفي عربي سني- فارسي شيعي؛ وإلى صراع قومي عربي- كردي، وذلك من خلال تعظيم "الخطر الإيراني" وتمكين الأكراد والاعتماد عليهم في العراق وسورية، وإعطائهم دوراً سياسياً وعسكريأً أكبر من حجمهم وإمكاناتهم وقدراتهم الحقيقية في المنطقة. The process of hitting the Syrian security and stability did not occur directly, but underwent several preliminary stages reflected in one way or another the importance and difficulty of targeting Syria, due to the overlap of some regional and international files in Syria. This had to be done through many steps; the US policy has sought to shift the direction of the conflict in the region of from an Arab-Israeli conflict into a sectarian Arab-Sunni- Persian Shiite conflict; and to a national conflict of Arab-Kurdish by maximizing the Iranian threat and empowering the Kurds in Iraq and Syria and giving them a political and military role greater than their size and potential and their true capabilities in the region.